Consensus on Exercise Reporting Template (CERT): Modified Delphi Study. Issue 10 (1st October 2016) - Slade, Susan C.; Dionne, Clermont E.; Underwood, Martin; Buchbinder, Rachelle; Beck, Belinda; Bennell, Kim; Brosseau, Lucie; Costa, Leonardo; Cramp, Fiona; Cup, Edith; Feehan, Lynne; Ferreira, Manuela; et al.
Abstract: Background: Exercise interventions are often incompletely described in reports of clinical trials, hampering evaluation of results and replication and implementation into practice. Objective: The aim of this study was to develop a standardized method for reporting exercise programs in clinical trials: the Consensus on Exercise Reporting Template (CERT). Design and Methods: Using the EQUATOR Network's methodological framework, 137 exercise experts were invited to participate in a Delphi consensus study. A list of 41 items was identified from a meta-epidemiologic study of 73 systematic reviews of exercise. For each item, participants indicated agreement on an 11-point rating scale. Consensus for item inclusion was defined a priori as greater than 70% agreement of respondents rating an item 7 or above. Three sequential rounds of anonymous online questionnaires and a Delphi workshop were used. Results: There were 57 (response rate=42%), 54 (response rate=95%), and 49 (response rate=91%) respondents to rounds 1 through 3, respectively, from 11 countries and a range of disciplines. In round 1, 2 items were excluded; 24 items reached consensus for inclusion (8 items accepted in original format), and 16 items were revised in response to participant suggestions. Of 14 items in round 2, 3 were excluded, 11 reached consensus for inclusion (4 items accepted in original format), and 7 were reworded. Sixteen items were included in round 3, and all items reached greater than 70% consensus for inclusion. Limitations: The views of included Delphi panelists may differ from those of experts who declined participation and may not fully represent the views of all exercise experts. Conclusions: The CERT, a 16-item checklist developed by an international panel of exercise experts, is designed to improve the reporting of exercise programs in all evaluative study designs and contains 7 categories: materials, provider, delivery, location, dosage, tailoring, and compliance. The CERT will encourage transparency, improve trial interpretation and replication, and facilitate implementation of effective exercise interventions into practice.